Penyuluhan Dan Penerapan Protokol Kesehatan Untuk Menekan Laju Pandemi Coronavirus Disease-19 Di Kampus Institut Transportasi Dan Logistik Trisakti - Reza Aditya Digambiro; Edy Parwanto (CV. Multi Kreasi Media, 2023)
The implementation of outreach activities at Institut Transportasi dan Logistik (ITL) Trisakti focuses on a holistic approach to facing the Coronavirus Disease-19 (COVID-19) pandemic. The main problem faced by the ITL Trisakti Academic Community is a lack of comprehensive understanding of health protocols and the long-term impacts of the pandemic. Facing globalization and the need to adapt to the pandemic, the academic community needs to be equipped with knowledge and skills to face these challenges. The purpose of this activity is to increase the awareness and knowledge of the ITL Trisakti Academic Community about COVID-19through mentoring and counseling. The methods used include outreach, training, mentoring, and evaluation during the November 2020 period. The results of this activity show that the understanding and awareness of the academic community have increased, and the implementation of health protocols has improved on campus.